A general modeling framework for FO spiral-wound membrane and its fouling impact on FO-RO desalination system - Goi, Y. K.; Liang, Y. Y. (Elsevier, 2025)
Modeling fouling in forward osmosis (FO) spiral-wound membrane (SWM) is challenging due to the time-dependent nature of fouling and the complex flow patterns induced by baffle. This necessitates the development of a general modeling framework for FO SWM module that prioritizes both accuracy and ease of implementation. This framework was validated against FO SWM experiment data from previous work, demonstrating a reasonable agreement with a maximum error of 13.1 % in FO permeate flux. This validated model was used to study the impact of fouling on feed recovery, a critical factor influencing specific energy consumption (SEC) in FO-RO desalination systems. While improved operating conditions and membrane parameters (A, Ss and Cf) initially lead to increased water flux, this effect was significantly counteracted by accelerated fouling. Consequently, performance improvements in terms of flux and SEC remained minimal (<1 %) under severe fouling conditions. The results show that for foulant cake with larger pore diameter (>10 nm), the contribution of hydraulic resistance is insignificant compared to osmotic resistance. However, the contribution of hydraulic resistance becomes important for foulant cakes with pore diameter smaller than 10 nm. This paper shows that modeling have evolved to a stage that they can be used to understand membrane fouling phenomena at the SWM module scale.